Investigation of the photocatalytic activity of titanium dioxide films under visible light measured by electrospray mass spectrometry. (18th October 2018) - Souza, Diego H. P.; Guimarães, Robson R.; Correra, Thiago C.; Zamarion, Vitor M.
Abstract : Pure TiO2 P-25 films demonstrate effective photodegradation activity of organic pollutants under the incidence of visible light observed via ESI(−)-MS. Abstract : We report, for the first time, the photocatalytic activity of pure TiO2 P-25 in the form of thin homogeneous mesoporous films under visible light activation. The study was accomplished by analyzing the photodegradation rate of two water contaminant molecules, 2-naphthol and methyl orange, via an electrospray mass spectrometry technique with the use of ammonium hexafluorophosphate as an internal standard. The employed methodology can also be used to run different semiquantitative assays and study other film mediated photocatalytic processes. It was observed that TiO2 films can easily promote photooxidation of 2-naphthol under the incidence of visible light and in the presence of oxygen gas by showing almost complete photodegradation after about 6 hours of reaction. Photooxidation of methyl orange was also observed, yet the decay rate was slower. This process was also confirmed through identification of by-products of the reaction via mass spectrometry and through the decay of the absorbance peak at 468 nm via UV-vis spectrophotometry. This photoactivity of pure TiO2 P-25 films under visible light is attributed to its narrower band gap that occurs because of the thermal treatment that titania undergoes in the process of synthesis of the films. The use of these films as photocatalysts is an advantage since they work as a heterogenous catalyst in the absence of UV radiation.